2011
DOI: 10.1007/s00221-011-2934-2
|View full text |Cite
|
Sign up to set email alerts
|

Manual matching of perceived surface orientation is affected by arm posture: evidence of calibration between proprioception and visual experience in near space

Abstract: Proprioception of hand orientation (orientation production using the hand) is compared with manual matching of visual orientation (visual surface matching using the hand) in two experiments. In Experiment 1, using self-selected arm postures, the proportions of wrist and elbow flexion spontaneously used to orient the pitch of the hand (20% and 80% respectively) are relatively similar across both manual matching tasks and manual orientation production tasks for most participants. Proprioceptive error closely mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…With regard to perceived slant, evidence of consistent and systematic orientation biases have been reported in the haptic perception of slant (Durgin & Li, 2012 ; Hajnal, Abdul-Malak, & Durgin, 2011 ; Shaffer & McManama, 2015 ) as well as in the proprioception of hand orientation (Li & Durgin, 2012b ). With respect to perceived azimuth direction, angular scale expansion has additionally been discovered in the vestibular perception of heading direction (e.g., Cuturi & MacNeilage, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…With regard to perceived slant, evidence of consistent and systematic orientation biases have been reported in the haptic perception of slant (Durgin & Li, 2012 ; Hajnal, Abdul-Malak, & Durgin, 2011 ; Shaffer & McManama, 2015 ) as well as in the proprioception of hand orientation (Li & Durgin, 2012b ). With respect to perceived azimuth direction, angular scale expansion has additionally been discovered in the vestibular perception of heading direction (e.g., Cuturi & MacNeilage, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…One is that the haptic measure may be limited by biomechanics (cf. Li & Durgin, 2012) that prevented a genuine increase in perceived slant to be measured. Another is that the haptic measure could be driven by processing in the dorsal pathway (cf.…”
Section: Resultsmentioning
confidence: 99%
“…This free hand method of manual matching has been shown to be much more sensitive than the traditional palm board -- perhaps because it removes many of the artificial biomechanical constraints associated with palm boards. Li and Durgin (2011a) showed that free hand manual matching techniques were correlated with verbal reports (see also Li & Durgin, 2011b). For near surfaces manual gestures tend to be quite well calibrated whereas, like verbal methods, they overestimate far surfaces (see Li & Durgin, 2010).…”
Section: Methodsmentioning
confidence: 95%